Women and Marriage in Paul and his Early Interpreters. By Gillian Beattie - Gooder, Paula (The journal of theological studies, 2007)
Like many volumes in this series, this monograph arose out of doctoral research, in this case Gillian Beattie's at Manchester University. The aim of the research is to explore how Paul's writings on women and marriage were understood by certain early interpreters. Beattie made the interesting choice of following these themes in the deutero-Pauline texts of Colossians, Ephesians, and the Pastoral epistles and in certain Nag Hammadi texts. Out of this main aim a secondary issue emerged, which Beattie explores in Part III of her work, which is that the Nag Hammadi material should be read in its own right as a legitimate early interpretation of Paul, and not through the eyes of opponents such as Irenaeus and Tertullian., The monograph falls into three major sections.